Pharmacodynamic genetic variants related to antipsychotic adverse reactions in healthy volunteers. (July 2013) - López-Rodríguez, Rosario; Cabaleiro, Teresa; Ochoa, Dolores; Román, Manuel; Borobia, Alberto M; Carcas, Antonio J; Ayuso, Carmen; Novalbos, Jesús; Abad-Santos, Francisco
Aim: Clinical trials with healthy volunteers are a useful model for evaluating safety and tolerability, without the interference of concomitant diseases and drugs. The present study aims to improve our understanding of antipsychotic-related adverse reactions (ARs) and their possible association with common genetic variants of pharmacodynamic proteins such as neurotransmitter receptors/transporters.Materials & methods: A total of eight polymorphisms located in seven pharmacodynamic-related genes ( SCL6A4, MDR1, 5HT2A, DRD2, DRD3, COMT and GRIN2B ) were genotyped in a cohort of 211 healthy volunteers who received a single dose of risperidone (1 mg), olanzapine (5 mg) or quetiapine (25 mg).Results: Interestingly, a significant association was found between the incidence of neurological ARs and specific polymorphisms in key genes ( DRD2 and SCL6A4 ).Conclusion: Genetic variants in pharmacodynamic genes could represent valuable markers of AR risk and antipsychotic safety. Original submitted 7 February 2013; Revision submitted 3 June 2013